Status of the Right to Health Care During the Covid-19 in Asia Under International Law - ELSHOBAKE, MOHAMMED R. M. (Advances in Humanities and Contemporary Studies, 2024)
On January 30, 2020, the World Health Organization declared that the spread of COVID-19 is a public health emergency of international concern. Then, on March 11, 2020, the World Health Organization announced that COVID-19 is a global pandemic, calling on all countries to strive to confront it and limit its spread. As soon as COVID-19 was declared a global pandemic, the governments of all countries rushed to take strict measures, under the pretext of preventing the spread of the pandemic. International human rights law recognises in exceptional situations and serious threats to public health and public emergencies, such as wars, natural disasters, and epidemics, to restrict and suspend some rights to protect another higher right, which is the right to life, and to prevent any threats to public health. This paper will discuss the status of the right to health care during the spread of COVID-19 in some Asian countries. Through doctrinal and legal study and content analysis, this paper will analyse the important relevant legal provisions under international human rights law and applies these provisions to the reality of managing the COVID-19 crisis to identify the most prominent human rights violations to the right to health care in Asia during the COVID-19 outbreak. The Universal Declaration of Human Rights (UDHR), the ICCPR and the International Covenant on Economic Social and Cultural Rights will be used as a standard for the definition of relevant human rights. It is concluded that the COVID-19 pandemic has posed unprecedented challenges to global health systems, and its impact on the right to health care has been profound. In addition, this pandemic has shown the ugly fractures in health-care systems, health inequities, racism, and discrimination. The benefit of this paper is to provide recommendations that protect human rights during pandemics.